Tugas Hidup Manusia dan Peranan Manajemen Pendidikan - Toha Ma'sum dan M. Munir (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2020)
Humans are the most perfect creatures created by Allah SWT compared to other creatures. In its creation, humans carry out duties as caliphs on earth, in addition to carrying out the duties of duty to worship, as the main purpose of its creation. In carrying out their duties, humans need the provision of knowledge and knowledge, which can go through the educational process, where this process is a lifelong human obligation. The education process, which is the main means of success or the implementation of the task of human life, must be carried out in a planned, organized, carried out and supervised together by 3 (three) education centers (tripusat), namely the family, educational institutions, and the community. Effective and efficient managerial activities in carrying out management functions of the components of education implementation, bearing in mind the key to educational success is that.